Is intergenerational care associated with depression in older adults? - Han, Shurong; Guo, Jiahui; Xiang, Jianjun (Frontiers in Public Health, 2024)
(1) Background: It has become an alarming issue that the elderly in China are facing mental health issues, causing severe depression. In this context, intergenerational care, in which grandparents care for young children instead of the young parents, is gaining importance. This study aims to explore the correlation between intergenerational care and depression among the elderly, seeking alternative approaches to enhancing their quality of life. This study concludes that intergenerational care is an effective strategy for promoting active aging. (2) Methods: This study used multiple linear regression, propensity score matching, and additional analysis of heterogeneity, mediation, and moderation effects, with data from the 2018 CHARLS survey. (3) Results: The results indicated a negative correlation between intergenerational care and depression among the elderly. The correlation was stronger for females and younger elderly people. Additionally, social activities served as a mediator between intergenerational care and depression among the elderly, and health satisfaction positively moderated this relationship. (4) Conclusion: This study posits that intergenerational care serves as an effective approach for promoting active aging. It emphasizes the necessity for supportive government policies and community-family collaborations to encourage intergenerational care and its beneficial impact on mental health among the elderly.